Disciples, Devotees, Scholars, and Friends - Pottgiesser, Uta; Quist, Wido (Journal / Docomomo International)
It is a long-standing and well-appreciated tradition of Docomomo International to emphasize its diversity expressed in buildings, sites, and neighborhoods due to different geography, language, education, and personalities. The term multiple modernisms has been coined to express regional, stylistic, and constructive differences in the formal and philosophical expression of Modern Movement across the globe, within the continents, and even within countries. Docomomo conferences and Docomomo Journals have used and interpreted the term over the last 30 years to express and acknowledge the diversity in the growing community of national working parties. We only need to refer to the recent Docomomo Journal no. 67 (2022) on Multiple Modernities in Ukraine1, or no. 36 (2007) on Other Modernisms2, published in parallel with the 2006 Docomomo International Conference in Istanbul and Ankara (Turkey) with the same title. Other issues highlighted local and regional particularities together and, at the same time, referenced common roots and personal links, such as the preservation technology dossier no. 13 on Perceived Technologies in the Modern Movement 1918-1975 published by the International Specialist Committee on Technology (ISC/T) in 2014. In that publication, the specific and long-term collaborations of architects with engineers and artists were explored often leading to exceptional solutions in structure, design, and function.